Indian Muslims: past, present and future - Bandukwala, J.s. (2006)
Centuries of insecurity drove Muslims in India away from the very forces - English, science and modernity - that would have helped them cope with the changing world. Now at last - in the aftermath of the Babri masjid demolition and the Gujarat killings - they have begun emphasising the need for a modern education. There is much more that needs to be done - on the gender imbalance, family planning and attitudes to divborce - and Muslims have to fight their ghettoisation in the cities and towns. Goodwill and understanding between members of the two main religions in India is, of course, necessary to help the Muslims in their struggle for a place of honour in the Indian sun. - Reproduced.
Keywords: Muslims - India; Muslims